Sompoton: Sabah Bamboo Mouth Organ - Sinin, Hamdan; Md Rezaur, Rahman; Khairul Anwar, Mohamad Said; Ana Sakura, Zainal Abidin; Ahmad Fauzi, Musib (N State Univerity, 2022)
This study considered the Sabah traditional bamboo musical instrument, sompoton. The fast Fourier transform (FFT) of sompoton was determined via a Pico oscilloscope. All three sompotons displayed almost similar fundamental frequencies. The individual tubes 1, 2, 3, 4, 5, 6, and 8 (except tube 7) of sompoton I, II, and III produced the fundamental frequency (in hertz) as 924, 758, 655, 589, 449, 407, 537, as 954, 779, 655, 614, 469, 387, 552, and as 944, 820, 655, 635, 407, 407, and 552, respectively. The averaged frequency obtained from the three sompotons (with the diatonic frequency and note in bracket) was 940.6 (932.3-A5# tube 1), 785.6 (783.9-G5 tube 2), 655 (659.2-E5 tube 3), 612.6 (622.2-D5# tube 4), 547 (554.3-C5# tube 8), 441.6 (440-A4 tube 5), and 400.3 (392- G4 tube 6). The tunings were remarkably similar in the tonal relationships. The pitch of the drone tube (tube 6) repeated an octave higher at tube 2, the intervals of perfect 4th higher at tube 8, and the intervals of perfect 5th higher at tube 4 were always found. The standard deviations of the fundamental pitch from the three sompotons for tube 1, 2, 3, 4, 5, 6, and 8 were 15.3, 31.5, 0.0, 9.2, 31.6, 11.5, and 8.7, respectively.